Food and Mind - Adhikari, Jamuna (Journal of Nursing Education of Nepal, 2023)
The objective of this review article is to describe the difference effects of vegetarian and non-vegetarian foods in body and mind.“As the food so is the mind” goes the ancient saying signifying that food is an essential ingredientin creating us. The nature of our diet impacts how we think and therefore crucial to what we become. In many religions where non-violence is regarded as a high principle, non-vegetariandiet is strictly forbidden not only just because it causes pain and suffering to other living creatures but also because it is the source of vicious thoughts and attitudes to its consumers.In other words, non-vegetarian lifestyles, a way of living where vices dwell comfortably. Thetrend of consumption of flesh by human beings is a pointer to several notions. It highlights theway we look at other organisms and our desire to overpower them. It symbolizes our inflatedego that brings our feeling as human as the centre of the universe. It presents our desire to cultivate nature for our gains. We rear the baby got so lovingly for one day to kill. It suggestsa belief system that justifies violence in the name of need and necessity. No peace marches,diplomatic dialogues and conferences can bring peace to the planet when we are burdeningit with desperate (hopeless) cries of helpless creatures. For what we sow, so shall we reap(Rajyoga Education and Research Foundation, 2009).
Keywords: NA